Analysis of the Influence of Price Perception, Service Quality, and Advertising on Smartphone Purchasing Decisions at M-CEL OESAPA, Kupang City - Damaris Y. Koli; Endang Damaris Koli; Alfred G.O. Kase; Godlief F. Neonufa (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study is entitled "Analysis of the Effect of Price Perception, Service Quality, and Advertising on Smartphone Purchase Decisions at M-Cell Oesapa, Kupang City (A Case Study of the Kupang City Community)". The research problems examined are whether price perception affects smartphone purchase decisions at M-Cell Oesapa, Kupang City; whether service quality affects smartphone purchase decisions at M-Cell Oesapa, Kupang City; and whether advertising affects smartphone purchase decisions at M-Cell Oesapa, Kupang City. The objectives of this study are to determine the effect of price perception, service quality, and advertising on smartphone purchase decisions at M-Cell Oesapa, Kupang City. The population of this study consists of all people in Kupang City who have purchased smartphones at M-Cell Oesapa, Kupang City. Since the population size is unknown, the sample was determined using the Rao Purba formula, resulting in 96 respondents. Data were collected using a questionnaire distributed via Google Forms. The data analysis techniques used include multiple linear regression analysis, partial t-test, simultaneous F-test, and the coefficient of determination (R²). The results show that partially, price perception has a positive and significant effect on smartphone purchase decisions at M-Cell Oesapa, Kupang City; partially, service quality has a positive and significant effect on such decisions; partially, advertising has a positive and significant effect; and simultaneously, price perception, service quality, and advertising together have a positive and significant effect on smartphone purchase decisions at M-Cell Oesapa, Kupang City.